Experience in diagnosis and treatment of duodenal ulcer perforation in children - Qiulong Shen; Tingting Liu; Siwei Wang; Li Wang; Dayong Wang (BMC, 2023)
Abstract Background This study aims to summarize our experience in diagnosis and treatment of pediatric duodenal ulcer perforation in a National Center for Children's Health. Methods Fifty-two children with duodenal perforation hospitalized in Beijing Children's Hospital Affiliated to Capital Medical University from January 2007 to December 2021 were retrospectively collected. According to the inclusion and exclusion criteria, patients with duodenal ulcer perforation were included in the group. They were divided into the surgery group and the conservative group according to whether they received surgery. Results A total of 45 cases (35 males and 10 females) were included, with a median age of 13.0 (0.3-15.4) years. Forty cases (40/45, 88.9%) were over 6 years old, and 31 (31/45, 68.9%) were over 12 years old. Among the 45 cases, 32 cases (32/45, 71.1%) were examined for Helicobacter pylori (HP), and 25 (25/32, 78.1%) were positive. There were 13 cases in the surgery group and 32 cases in the conservative group, without a significant difference in age between the two groups (P = 0.625). All cases in the surgery group and the conservative group started with abdominal pain. The proportion of history time within 24 h in the two groups was 6/13 and 12/32 (P = 0.739), and the proportion of fever was 11/13 and 21/32 (P = 0.362). The proportion of pneumoperitoneum in the surgery group was higher than that in the conservative group (12/13 vs. 15/32, P = 0.013). The fasting days in the surgery group were shorter than those in the conservative group (7.7 ± 2.92 vs. 10.3 ± 2.78 days, P = 0.014). There was no significant difference in the total hospital stay (13.6 ± 5.60 vs14.8 ± 4.60 days, P = 0.531). The operation methods used in the surgery group were all simple sutures through laparotomy (9 cases) or laparoscopy (4 cases). All patients recovered smoothly after surgery. Conclusion Duodenal ulcer perforation in children is more common in adolescents, and HP infection is the main cause. Conservative treatment is safe and feasible, but the fasting time is longer than the surgery group. A simple suture is the main management for the surgery group.